Comparing of pre- and post- financial crisis credit risk disclosure in banking institutions - YU, Tianyi (2011)
Recently, an increasing amount of studies which are related to the issue of risk disclosures have drawn considerable attention. Moreover, since the late – 2007, the appearance of the international financial market turmoil has also made the important role played by risk and risk management in the international financial area more and more significant and put the importance of risk disclosures into a higher degree, especially the risk reporting of credit risk. This dissertation examines and analyzes credit risk disclosures practices in the annual reports of banking sectors within four different countries (UK, US, China and Brazil) for the financial year of 2006 and 2010. The purpose of this study is to find out whether has banks‟ credit risk disclosures practice changed after the recent financial crisis and whether there is certain gap of this kind of disclosures practice among different countries. Additionally, this dissertation also examines the determinants of credit risk reporting. Following a content analysis and regression analysis, the results show that banking sectors‟ overall performance on credit risk disclosures have significantly improved since the appearance of financial crisis and developed countries‟ degree of credit risk reporting is always higher than developing countries‟. Meanwhile, a significant association is found between the level of credit risk disclosures and bank size; however, no significant association is proved by this study between the degree of credit risk reporting and the determinant of the level of risk. Keywords: Risk; Risk management; Risk disclosures; Credit Risk disclosure; Banking sector;